Evaluating the effectiveness of eia process in promoting sustainable development objectives (social aspects) : the case of transnet soc - Mkateko, Marilele (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.